Protestant Ethics in Academia - Kucharska, Anna Maria (Journal of Education Culture and Society, 2020)
Academic ethics has recently become an important issue in Poland. With changes in the Polish law on higher education a new approach to ethics of students and academics has been presented. As a PhD student and young researcher, I am personally interested in the introduced changes. This article seeks to examine professional academic ethics in terms of two chosen theories, that is, the Protestant work ethic of Max Weber and its adaptation to the academic environment by Robert K. Merton. I situate both theories in the Polish context of shaping the academic ethos. In my deliberations I recall Dietrich Bonhoeffer’s works as fundamental for the Protestant work ethos values, which are honesty, reliability and diligence. Additionally I present their religious as well as non religious aspects. With such theoretical foundations, I attempt to evaluate the risks and violations in the ranks of Polish academics. The theoretical basis and the collected data enable me to put forward the claim that it is not feasible in Poland to follow the Western model of work ethics. Instead, it has to be built from scratch. To start this process, we need to consider the value of responsibility as a crucial category not only for the process of academic ethos formation, but also for everyday life from the early years.